Penerapan Metode TAM dalam Menganalisis Pengaruh Media Sosial terhadap Perkembangan Teknologi pada Siswa SMPIT IQRO' - Putri, Halimatussa’diyah; Ningsih, Rahayu; Wahidin, Ahmad Jurnaidi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This study uses the Technology Acceptance Model to examine the development of social media technology and its impact on the lifestyle of SMPIT IQRO' students in Bekasi. It aims to analyze the influence of social media on the behavior of SMPIT IQRO' students in adopting technology, particularly through the Technology Acceptance Model (TAM) approach. The method used is descriptive quantitative research, involving 35 randomly selected respondents from the student population. Data were collected through an online questionnaire containing 58 statements related to Perceived Usefulness (POU), Perceived Ease of Use (PEU), and Behavioral Intention to Use (BIU). Data analysis was conducted using IBM SPSS version 26, with linear regression tests to measure the relationships between these variables. The results show that both POU and PEU have a positive and significant influence on BIU, with t-statistics values greater than the t-table and a significance level below 0.05. In conclusion, SMPIT IQRO' students have a high interest in using social media due to its perceived usefulness and ease of use, indicating that social media has the potential to support their learning. However, excessive use requires monitoring to minimize negative impacts.